2013
DOI: 10.13005/ojc/290302
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting Nanostructures and Nanocomposites for the Recognition of Toxic Chemicals (A Review)

Abstract: Semiconductor nanomaterials have attracted significant attention inresearch and applications in areas including energy conversion, sensing, electronics, photonics, and biomedicine. The parameters suchas size, shape, and surface characteristics of semiconducting nanomaterials are significant to control the properties for different applications.With the development of nanoscience and nanotechnology, one-dimensional (1D) semiconducting nanostructured materials including nanotubes, nanorods, nanosheets, nanoballs,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…The SPR band of ZnONPs decreases with increasing the pH of Regla seed extract to pH=11 accompanied by a red shift in the SPR band to 355 nm indicating the formation of smaller size uniform nanoparticles. Ameen et al (2013) [47] reported that the appearance of an SPR band in the region 300-400 nm confirmed the formation of ZnONPs. This shorter wavelength indicates that the particles have smaller sizes (see below).…”
Section: Effect Of Portulaca Oleracea (Regla Seeds) Extract Phmentioning
confidence: 99%
“…The SPR band of ZnONPs decreases with increasing the pH of Regla seed extract to pH=11 accompanied by a red shift in the SPR band to 355 nm indicating the formation of smaller size uniform nanoparticles. Ameen et al (2013) [47] reported that the appearance of an SPR band in the region 300-400 nm confirmed the formation of ZnONPs. This shorter wavelength indicates that the particles have smaller sizes (see below).…”
Section: Effect Of Portulaca Oleracea (Regla Seeds) Extract Phmentioning
confidence: 99%
“…The conductivities of CPs can be altered by modifying the electronic structures through doping or de-doping processes [9,10]. The fabrication of efficient chemical sensor using CPs as a sensitive material can provide the active working electrode and fast response towards the detection of either important or harmful chemicals [11,12]. Polypyrrole (PPy), Polythiophene (PTh), poly-1, 5-diaminonaphthalene (PDAN) and polyaniline (PANI) are regarded as potential CPs for chemical sensor fabrication.…”
Section: Introductionmentioning
confidence: 99%
“…of modified electrodes [31][32][33][34] . EIS on PAni and its derivatives modified electrodes have been reported [34][35][36][37] This work reports on the electrochemical behaviour and catalytic ability of poly(Ani-co-oPDA) modified CG electrode towards electro-oxidation of AA.…”
Section: Introductionmentioning
confidence: 99%